The Impact of The Proper Gold Rating Announcement on Stock Prices of Companies Listed on The IDX In 2023 - Junanto, Try; Endah Lestari, Retno Martanti; Widyowati, Mutiara Puspa; Herdiyana, Herdiyana (International Journal of Management Science and Information Technology, 2026)
Environmental degradation caused by industrial activities has led the Indonesian government to introduce the Company Performance Rating Program (PROPER), with the gold rating as its highest recognition. This study examines the effect of the PROPER Gold announcement (December 20, 2023) on the stock prices of companies listed on the Indonesia Stock Exchange. The research applies an event study method with a causal-comparative approach. The observation window spans 15 trading days (t−7 to t+7), involving 8 companies awarded the PROPER Gold rating in 2023, selected through purposive sampling. Daily closing stock prices were obtained from IDX publications. The Kolmogorov-Smirnov test was employed to assess data normality, and the Wilcoxon Signed Rank Test was used for non-normal distributions. Descriptive analysis was conducted to observe stock price trends before and after the event. Results indicate a tendency for stock price increases after the announcement, with a statistically significant difference between pre- and post-event prices, reflecting a positive market response.
Keywords: PROPER; Gold Rating; Event Study; Stock Price